Mitochondrial DNA typing of laser‐captured single sperm cells to differentiate individuals in a mixed semen stain. Issue 15 (11th July 2016) - Zhang, Lu; Ding, Mei; Pang, Hao; Xing, Jiaxin; Xuan, Jinfeng; Wang, Chunhong; Lin, Ziqing; Han, Song; Liang, Kewei; Li, Chunmei; Yao, Jun; Wang, Baojie
Abstract : The identification of individuals in a mixture of two semen samples usually involves an analysis of autosomal and Y chromosomal short tandem repeats (STR) which can exclude unrelated individuals but cannot achieve the purpose of individual identification. In sperm cells, there are multiple copies of mitochondrial DNAs (mtDNA) which exhibit genetic polymorphisms in different matrilineal‐related individuals. Single‐cell capture technology can be applied to obtain some single sperm cells in a mixed semen sample, then polymerase chain reaction can be employed to amplify the mtDNA hypervariable region I (HVR I) from each cell. By pooling the cells with the same HVR I sequence, we can obtain the sufficient nuclear DNA for STR typing.